1993
DOI: 10.1152/ajplung.1993.265.1.l45
|View full text |Cite
|
Sign up to set email alerts
|

Maturational changes induced by 1 alpha,25-dihydroxyvitamin D3 in type II cells from fetal rat lung explants

Abstract: Specific binding sites for 1 alpha,25 dihydroxyvitamin D3 [1 alpha,25-(OH)2D3] localized to type II pneumocytes have been evidenced in fetal rat lung at the end of gestation, suggesting a role for vitamin D3 in the control of lung maturation. In this study, we describe the morphological changes that occur in lung explants from 18-day-old rat fetuses grown for 1 and 2 days in control conditions and in the presence of 1 alpha,25(OH)2D3 (10(-9) M) or dexamethasone (10(-7) M). Point counting and planimetric measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
1
34
0
1
Order By: Relevance
“…Fibroblasts are recognized as influencing surfactant biosynthesis through paracrine actions. Before parturition, fibroblasts secrete a polypeptide that stimulates the rate-limiting enzyme for surfactant synthesis by the ATII cells (34,60,70). Perinatal lung maturation is a highly regulated process, and alveolar epithelialmesenchymal interactions play a critical role (90,96).…”
mentioning
confidence: 99%
“…Fibroblasts are recognized as influencing surfactant biosynthesis through paracrine actions. Before parturition, fibroblasts secrete a polypeptide that stimulates the rate-limiting enzyme for surfactant synthesis by the ATII cells (34,60,70). Perinatal lung maturation is a highly regulated process, and alveolar epithelialmesenchymal interactions play a critical role (90,96).…”
mentioning
confidence: 99%
“…In fetal rat lung, 1,25(OH) 2 D 3 increases the synthesis and secretion of surfactant lipids (34,35) and accelerates the appearance of the morphological features of alveolar type II cells (34). Rat alveolar type II cells have been shown to contain the nuclear hormone receptor for 1,25(OH) 2 D 3 , which is responsible for many of its physiological effects (38).…”
mentioning
confidence: 99%
“…[25][26][27][28][29] Specific binding sites for 1,25(OH)2D3 localized to type II pneumocytes have been found in fetal rat lungs and it has been shown that vitamin D accelerates type II pneumocyte maturation, increases the surfactant synthesis and secretion and has a critical role in epithelialmesenchymal interaction during lung growth. 17,18 In probable pathophysiology of TTN, immaturity of epithelial sodium channels (ENaC) is now believed to be major factor in failure of lung fluid resorption. A surge in catecholamines and endogenous steroids increase the expression and activity of ENaC.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, in fetal rat lung, vitamin D increases the synthesis and secretion of surfactant lipids and proteins in alveolar type II cells. 17,18 As role of vitamin D in TTN has not been studied much, so we conducted present study in our hospital to find the association between serum vitamin D levels and TTN.…”
Section: 13mentioning
confidence: 98%